Implementing intellectual curatorial strategy on Cinema Paradesa film screening program - Tunggul Banjaransari; Ahmad Syihan Herlambang (ProTVF, 2023)
Background: This article results from a film screening program creation activity held in Kupang village, Semarang Regency. Many efforts have already been made through film screening, has yet to have a comprehensive approach to screening. Thus, that activity is not correct on target. Purpose: To explain that a film is entertaining and can improve intimate communication between parents and children. Methods: Intellectual curatorial strategy was applied. This method uses 6 Key Performance Indicators (KPI). These six indicators are audience diversity, film diversity, social engagement, uniqueness, popularity, and excellence. It becomes a reference for the writers to design a measured and definitive program to reach goals. Results: Two aspects become the results of this screening program. The first aspect film has successfully triggered the audience to express their personal life actively. The second aspect, the film screening program with the KPI’s intellectual curatorial strategy, proves that films are not only focused on entertaining, seeking audiences to be box office and profit-oriented. Implications: This screening program is intended to foster audience interaction. The outcome exceeds this achievement, not only in terms of communication but also in terms of the audience’s feelings, which can be expressed to form a warm interaction.